Wild Idea : Buffalo and Family in a Difficult Land - O'Brien, Dan, 1947- (Book collections on Project MUSE., 2014)
For more than forty years the prairies of South Dakota have been Dan O'Brien's home. Working as a writer and an endangered-species biologist, he became convinced that returning grass-fed, free-roaming buffalo to the grasslands of the northern plains would return natural balance to the region and reestablish the undulating prairie lost through poor land management and overzealous farming. In 1998 he bought his first buffalo and began the task of converting a little cattle ranch into an ethically run buffalo ranch. Wild Idea is a book about how good food cho.